A Companion to Schubert's Schwanengesang: History, Poets, Analysis, Performance - Chusid, Martin (New Haven, CT Yale University Press, 2000)
Schwanengesang, collected as a song "cycle" and published shortly after Schubert's death, is one of the composer's most beloved works. In this book Martin Chusid and other distinguished Schubert scholars and performers -- Edward T. Cone, Walther Durr, Walburga Litschauer, and Steven Lubin -- provide a rich appreciation of the musical and literary qualities of these miniature masterpieces.The Companion contains commentaries on each of the fourteen songs as well as essays on performing the song cycle, the three poets who wrote the lyrics (Rellstab, Heine, and Seidl), and issues surrounding the formal structure of the cycle and reordering of the Heine songs. Also included in the volume is the complete original German poetry with a new English translation, a critical examination of the existing literature about each song, a list by Richard LeSueur of all the complete recordings of the cycle on LP and CD, and an extensive bibliography.
Keywords: Schubert, Franz -- 1797-1828; 19th Century (1801-1900); Music history; Musical analysis; Song; Poetry; Vienna (Austria)